Analysis of a Gigantic Jet in Southern China: Morphology, Meteorology, Storm Evolution, Lightning, and Narrow Bipolar Events. Issue 15 (1st August 2020) - Yang, Jing; Qie, Xiushu; Zhong, Lihua; He, Qijia; Lu, Gaopeng; Wang, Zhichao; Wang, Yu; Liu, Ningyu; Liu, Feifan; Peng, Kang‐Ming; Zhu, Baoyou; Huang, Anjing; et al.
Abstract: At about 22:43:30 BJT (Beijing Time = UTC + 8) on 13 August 2016, two amateur astronomers in Shikengkong, Guangdong province, and Jiahe County, Hunan province, respectively, fortuitously captured a gigantic jet (GJ) event simultaneously, and the GJ exact location could be triangulated. The parent thunderstorm was in a very humid environment (Precipitable Water [PWAT] in excess of 60 mm), featuring high convective available potential energy (CAPE of 2, 428 J/kg). The GJ occurred in the region with the coldest cloud top brightness temperature of −64 °C, suggesting the GJ was associated with strong vertical development of the thunderstorm. The vertical cross sections of radar reflectivity also show that the GJ occurred near the thunderstorm strong convection region (overshooting top). The negative cloud‐to‐ground flashes dominated during the thunderstorm evolution. Three positive narrow bipolar events (NBEs) were detected within 30 s before and after the GJ. It indicates that the NBEs were occurred in the upper and middle layers of the thunderstorm (altitude of 11–13 km) with radar reflectivity of 30–35 dBZ. Key Points: The location of a gigantic jet was triangulated using photographs The jet occurred just after the peak of a convective pulse Three narrow bipolar events clustered around the jet time